Uzbekistan's experience in achievement of sustainable development in the regions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the experience of the Republic of Uzbekistan in achieving sustainable development in the regions of the country. Examples of effective improvements in condition and position in several global and national sustainable development goals by country are provided.